Treatment Options in Hemophilia - Miesbach, Wolfgang (Dtsch Arztebl Int, 2019)
BACKGROUND: Approximately 4550 persons were under treatment for hemophilia in Germany in 2017. The condition is currently treated with intravenous supplementation of the missing clotting factor, either prophylactically or as needed. Newer treatment options rely on novel mechanisms of action. METHODS: This review is based on pertinent publications retrieved by a selective search in MEDLINE/PubMed, as well as on expert opinions and the recommendations of specialty societies. RESULTS: Randomized controlled trials have shown that, in children aged 30 months to 6 years, prophylactic clotting-factor supplementation yields a markedly lower annual rate of hemorrhage than supplementation as needed: 3.27 (standard deviation [SD] 6.24) for the former vs. 17.69 (SD 9.25) for the latter. A similar large effect was seen in patients aged 12 to 50 years, with hemorrhage rates of 1.9 (SD 4.1) vs. 28.7 (SD 18.8). Clotting-factor preparations with longer half-lives make it possible to lessen the frequency of administration and to prevent subtherapeutic factor levels. A number of alternatives to clotting-factor supplementation have recently been approved or are currently being clinically tested. These new drugs are injected subcutaneously and have a longer half-life, possibly enabling better protection against bleeding than the current standard treatment. A further advantage of some of these drugs is that they can be given even in the presence of inhibitors to factor VIII. In addition, initial (phase I) clinical trials of gene therapy have been performed successfully for both hemophilia A and hemophilia B. CONCLUSION: Now that new alternatives to classic supplementation therapy are becoming available, pertinent treatment algorithms for patients with hemophilia will have to be developed. It is still unclear to what extent the new drugs might supplant clotting factor supplementation as the first line of treatment.